Steven-Johnson syndrome and acute hepatitis induced by EBV infection : Case report - Thaninkitiwong, Sumalee (Journal of Preventive Medicine Association of Thailand, 2020)
Steven-Johnson syndrome (SJS) is a rare but severe dermatological condition and characterized by skin erythematous exanthema with possible evolution into vesiculobullous lesions and potentially induced by infectious agents (Mycoplasma pneumonia, Herpes simplex virus, Cytomegalovirus, EBV etc.) or drugs (anticonvulsants, antibiotics, NSAIDs etc.) and idiopathic causes. Infection is not a common cause of SJS although there have been case reports of Mycoplasma pneumonia but other infections such as herpes simplex virus, EBV is rare. EBV is in the same group as Herpes virus, causes infectious mononucleosis, usually found in adolescents and adults. This article reports a 43 years old woman who presented with fever for 4 days, erythema on the face, trunk and extremities. She was first diagnosed with fever with rash and was admitted for investigation and treatment. After a few days, she developed flaccid blisters on her trunk and forearms, painful erosions on tongue and buccal mucosa, hyperemia on both conjunctiva. Laboratory studies revealed high levels of serum aminotransferase, positive Anti-EBV (VCA) IgM serum and skin biopsy suggest to SJS. Finally, Steven-Johnson syndrome with acute hepatitis secondary to EBV infection was diagnosed. After 17 days of treatment, the patient had clinical improvement, the resolution of acute cutaneous manifestations and acute hepatitis had been for 1 month. The success of treatment depends on early recognition of the condition, prompt removal of the causative medications or infection and invasive supportive care in hospital. EBV may rarely associated with various patterns of skin eruptions but only a few cases of SJS and acute hepatitis induced by acute Epstien-Barr virus infection were diagnosed in the published literature.